Preserving the Integrity of Liposomes Prepared by Ethanol Injection upon Freeze-Drying: Insights from Combined Molecular Dynamics Simulations and Experimental Data - Silvia Franzè; Francesca Selmin; Paolo Rocco; Giuseppe Colombo; Antonella Casiraghi; Francesco Cilurzo (Pharmaceutics, 2020)
The freeze-drying of complex formulations, such as liposomes, is challenging, particularly if dispersions contain residual organic solvents. This work aimed to investigate the effects of possible protectants, namely sucrose, trehalose and/or poly(vinyl pyrrolidone) (PVP), on the main features of the dried product using a 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC)-based liposomal dispersion prepared by ethanol injection and containing ethanol up to 6%, as a model. The interactions among vesicles and protectants were preliminary screened by Molecular Dynamics (MD) simulations, which have been proved useful in rationalizing the selection of protectant(s). The freeze-drying protocol was based on calorimetric results. Overall data suggested a stronger cryo-protectant effect of trehalose, compared with sucrose, due to stronger interactions with the DPPC bilayer and the formation of highly ordered clusters around the lipids. The effect further improved in the presence of PVP. Differently from the other tested protectants, the selected trehalose/PVP combination allows to preserve liposome size, even in the presence of 6% ethanol, as demonstrated by Nanoparticle Tracking Analysis (NTA). Nevertheless, it should be also underlined that cakes blew out at an ethanol concentration higher than 1% v/v, probably due to the poor cohesion within the cake and solvent vapour pressure upon sublimation.